IMPROVING THE SEPARATOR DESIGN TO PREVENT COTTON FIBER LOSS: Cotton separation system - Salokhiddinova, Makhliyo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This scientific study addresses the problem of fiber loss in the cotton ginning industry, examining the scientific and practical basis for the structural improvement of the working chamber of the cotton air separator. The key innovation is the introduction of specialized trapezoidal guide vanes into the separator's inlet, which serve to minimize the mechanical contact between the cotton flow and the grid surfaces. The results of theoretical modeling and experimental analysis under industrial conditions confirmed the high efficiency of the proposed design. The implementation of the guide vanes significantly reduced the fiber loss coefficient: for I-II grades, from 0.70 kg/h to 0.28 kg/h (60 % reduction), and for lower-grade cotton (III-V), from 3.78 kg/h to 2.42 g/h. Comparative calculations indicated that the enterprise saves a total of 4,495.5 kg of cotton fiber over one year of operation. The monetary equivalent of this saved raw material is over 73 million Sum, ensuring a rapid payback for the equipment modernization costs.